Pendampingan Belajar Matematika Materi Pertidaksamaan Linear Satu Variabel di Kelas VII MTs Negeri Kerinci - Rahmadhani, Aulia Sefti; Putri, Latifa Intan Brilian; Amelia, Nurul; Fadhilah, Ulfa; Putra, Aan (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Several learning difficulties experienced by students at school are difficulty in solving the problems due to a lack of understanding of concepts, fear of being wrong and being scolded by the teacher, the initial assumption that mathematics is difficult, and a lack of understanding that resulting in conceptual errors. Assistance was carried out for VII B in MTs Negeri 2 Kerinci in detail on the Linear Inequalities in One Variable material. The assistance was carried out consisting of 4 assistants. Each assistants accompanies 2 students who have difficulty learning mathematics. Assistance activities for students run parallel to the learning carried out by the teacher. The assistants re-explains parts of the material that students who have learning difficulties have not understood and answers questions posed by the students they are accompanying. In addition, other examples are also given to increase understanding. This assistance have been carried out well and have provided positive benefits and impacts, namely the growth of enthusiasm for learning for students. This can be seen in the enthusiastic students who always ask about problem-solving.